PSXIII-12 Evaluation of split-time artificial insemination following administration of the 7-d CO-Synch + CIDR® estrus synchronization protocol in beef heifers. (5th December 2019) - Knickmeyer, Emma R; Thomas, Jordan M; Locke, James William C; Bonacker, Rachael C; Ellersieck, Mark R; Poock, Scott E; Smith, Michael F; Patterson, David J
Abstract: Estrous response and pregnancy rates resulting from fixed-time (FTAI) or split-time (STAI) artificial insemination were compared among heifers following treatment with the 7-d CO-Synch + CIDR ® (controlled internal drug release;1.38g progesterone) protocol. Heifers (n = 456) were assigned to balanced treatments based on weight and reproductive tract score (RTS; Scale 1–5). Gonadotropin-releasing hormone (GnRH; 100 µg gonadorelin acetate) was administered coincident with CIDR ® insertion. Progesterone inserts were removed after 7 d, and PG (250 mg im cloprostenol sodium) was administered at CIDR ® removal. Estrus detection aids (Estrotect ® ) were applied at the time PG was administered. Estrous status was recorded at FTAI or STAI, and estrus was defined as removal of ≥ 50% of the grey coating from the Estrotect ® patch. Heifers assigned to the FTAI treatment received GnRH and were artificially inseminated 54 h after PG administration. In the STAI treatment, only heifers that expressed estrus prior to 54 h were artificially inseminated at that time. For heifers failing to express estrus, AI was postponed 24 h and only those heifers that failed to exhibit estrus by the delayed time (78 h) received GnRH concurrent with AI. Estrous response prior to the standard time of FTAI did not differ between treatments (P = 0.3). Total estrous response was increased (P < 0.001) among heifers assigned to STAI (74%, STAI; 47%, FTAI); however, pregnancy rates resulting from AI were similar between treatments (48%, STAI; 46%, FTAI; P = 0.4), as were pregnancy rates at the end of a 60 d breeding season (P = 0.6). In summary, STAI resulted in a greater estrous response following treatment with the 7-d CO-Synch + CIDR ® protocol; however, this did not result in an increase in pregnancy rate compared to heifers that received FTAI.